2023
DOI: 10.1007/s11676-023-01670-x
|View full text |Cite
|
Sign up to set email alerts
|

Does ash dieback affect the reproductive ecology of Fraxinus excelsior L.?

Anna-Katharina Eisen,
Lisa Buchner,
Barbara Fussi
et al.

Abstract: Forest tree species reproduction is a key factor in maintaining the genetic diversity of future generations and the stability of forest ecosystems. The ongoing ash dieback disease could affect the reproductive ecology of Fraxinus excelsior L. and have a major impact on the quantity and quality of pollen and seeds. In this study, we investigated pollen production and viability of pollen and seeds of ash trees with different health status from 2018 to 2022. Inflorescences were collected from 105 trees (pollen pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
1
4
1
Order By: Relevance
“…However, as ash dieback induces the development of additional epicormic shoots during disease progression, further investigations explicitly studying the impact of epicormic shoots on pollen viability would give more insights. However, severely affected trees exhibited a substantial reduction in ower production, as demonstrated by Eisen et al (2024). This observation was con rmed in our study, as pollen samples could only be obtained from nine out of the total 119 trees from vitality score class 4 across all study sites and years.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, as ash dieback induces the development of additional epicormic shoots during disease progression, further investigations explicitly studying the impact of epicormic shoots on pollen viability would give more insights. However, severely affected trees exhibited a substantial reduction in ower production, as demonstrated by Eisen et al (2024). This observation was con rmed in our study, as pollen samples could only be obtained from nine out of the total 119 trees from vitality score class 4 across all study sites and years.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding the long generation times in natural forest landscapes, exploring pollen production is crucial as it provides valuable insights into phenomena such as the alternating patterns in mast and non-mast years (Dahl et al 2013). Additionally, it provides insights into the effects of air pollution or climate change (Ziska et al 2003; Darbah et al 2008;Talwar et al 2022) or the in uence of diseases (Kozlowski 1971;Eisen et al 2024). For example, CO, SO 2 , NO 2 and O 3 were often associated with negative effects on pollen production (Darbah et al 2008), while CO 2 repeatedly showed a positive effect (LaDeau and Clark 2006; Darbah et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations